There's a ghost in this house - Jeffers, Oliver (Penguin Group USA, 2021)
"A young girl lives in a haunted house, but she has never seen a ghost. Are they white with holes for eyes? Are they hard to see? Step inside and help the girl as she searches under the stairs, behind the sofa, and in the attic for the ghost." -- Amazon.